Students' needs reflected in the efl program: a small-scale evaluation of the methodologies proposed in an english program (2003)
In order to evaluate if there were discrepancies or not among the methodology proposed in the English program, students’ needs and what the teacher was actually doing in her classes, 13 ninth graders were asked to answer two questionnaires and they were also observed while they were in their English classes at the Institución Educativa Departamental El Vino (Cundinamarca, Colombia). The English teacher was also interviewed and a self- assessment questionnaire was given to her. The analysis of data showed that there were matches and mismatches among those three aspects. Key words: English-Teaching-Methods, English-Teaching-Programs-Evaluation, Second Language Acquisition-Teaching-Programs, Students-Teaching-Evaluation, Selfevaluation- Methodology Con el propósito de evaluar si existía o no concordancia entre las metodologías propuestas en el programa de inglés, las necesidades de los estudiantes y lo que la profesora realizaba en clase, trece estudiantes de noveno grado respondieron dos cuestionarios y fueron observados mientras estaban en su clases de inglés en la Institución Educativa Departamental El Vino (Cundinamarca, Colombia). De la misma forma, la profesora fue entrevistada y respondió un cuestionario de auto evaluación. El análisis de la información recogida mostró que había discrepancias y concordancias entre los tres aspectos anteriormente mencionados. Palabras clave: Inglés-Enseñanza-Métodos, Inglés-Enseñanza-Programas- Evaluación, Adquisición de segundo lenguaje-Enseñanza-Programas, Estudiantes-Enseñanza-Evaluación, Auto evaluación-Metodología